GP2015, a proposed etanercept biosimilar: Pharmacokinetic similarity to its reference product and comparison of its autoinjector device with prefilled syringes. (16th December 2016) - von Richter, Oliver; Skerjanec, Andrej; Afonso, Miguel; Sanguino Heinrich, Sabine; Poetzl, Johann; Woehling, Heike; Velinova, Maria; Koch, Annelize; Kollins, Dmitrij; Macke, Lars; Wuerth, Guido
Abstract : Aims: To assess pharmacokinetics (PK) and safety of GP2015, a proposed etanercept biosimilar, in two studies: comparison with etanercept originator (ETN, bioequivalence study ) and comparison of GP2015 administered via an autoinjector (AI) or prefilled syringes (PFS, delivery study ). Methods: Both studies were randomized, two‐sequence, two‐period, crossover studies conducted in healthy male subjects. In the bioequivalence study, subjects were randomized to receive a single 50 mg subcutaneous (s.c.) injection of GP2015 or ETN. In the delivery study, subjects were randomized to receive a single 50 mg s.c. injection of GP2015 via AI or PFS. Following a wash‐out period of 35 days, subjects in the bioequivalence study received single 50 mg s.c. injection of GP2015 or ETN, and subjects in the delivery study received single 50 mg s.c. injection of GP2015 via AI or PFS. Results: The geometric mean ratios (90% confidence interval) of GP2015/ETN for Cmax (1.11 [1.05–1.17]), AUC0–tlast (0.98 [0.94–1.02]) and AUC0–inf (0.96 [0.93–1.00]) were within the predefined bioequivalence range of 0.80–1.25. The geometric mean ratios (90% confidence interval) of AI/PFS for Cmax (1.01 [0.94–1.08]), AUC0–tlast (1.01 [0.95–1.07]) and AUC0–inf (1.01 [0.96–1.07]) were also within the range 0.80–1.25. No new safety issues were reported. Three subjects had low titres of non‐neutralising anti‐drug antibodies during a follow‐up visit in the bioequivalence study . Conclusions: The PK of GP2015 was similar to ETN, demonstrating bioequivalence. The safety profile of GP2015 was consistent with previous reports for ETN. The GP2015 AI provided equivalent dosing and tolerability to the GP2015 PFS.